1990
DOI: 10.1007/bf01740938
|View full text |Cite
|
Sign up to set email alerts
|

Major-histocompatibility-complex-class-II-positive cells and interleukin-2-dependent proliferation of immune T cells are required to reject carcinoma cells in the guinea pig

Abstract: Tumor immunity induced by bacillus Calmette-Guérin was studied in the line 10 hepatocellular carcinoma (line 10) in the strain-2 guinea pig. Line 10 immunity was investigated in vitro with a lymphocyte proliferation assay using line 10 tumor protein extracted with 3 M KCl and in vivo by adoptive transfer of line-10-immune spleen cells. Monoclonal antibodies against guinea pig leucocyte markers were used to block functional properties of the immune cells in order to determine which cell types or cell markers ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1991
1991
1993
1993

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…For the guinea-pig such a MHC class II antigen subtyping is not yet possible because of the lack of specific mAb. Recently we have shown that the cells expressing MHC class II antigen are needed for the recognition of the line 10 antigen in vitro and in vivo [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the guinea-pig such a MHC class II antigen subtyping is not yet possible because of the lack of specific mAb. Recently we have shown that the cells expressing MHC class II antigen are needed for the recognition of the line 10 antigen in vitro and in vivo [37].…”
Section: Discussionmentioning
confidence: 99%
“…For detection of various leucocyte populations the following mAbs were used: CT5 and T188, anti-(pan T cell) [2,6,38]; CT6, anti-(T suppressor/cytoxic cell) [25,37,38], and CT7, anit-(T pan T cell) [1,25,38], but recently described as an antibody to T-helper/inducer cells. MSgp9 and 31D2 are mAbs reacting with all B cells and with IgM B cells, respectively [10,25].…”
Section: Monoclonal Antibodies (Mabs)mentioning
confidence: 99%
“…The immunofluorescence was performed as described previously [27]. Pooled nucleated spleen cells (108 in 2 ml plain medium) of line-10-immune guinea pigs were transferred intracardially to naive recipients anaesthetized by an intramuscular injection of a mixture of Ketalar (20 mg/kg body weight, Parke Davis, Madrid, Spain.…”
Section: Methodsmentioning
confidence: 99%
“…O w i n g to the lack o f m A b s reacting with guinea pig T cell subpopulations, no particular T cell subpopulation m e d i a t i n g the rejection o f the line-10 t u m o u r has yet b e e n identified. W e recently s h o w e d in the line-10 t u m o u r m o d e l that the adoptive transfer o f line-10 i m m u n i t y is d e p e n d e n t on M H Cc l a s s -I I -a n t i g e n -p o s i t i v e cells and the p r e s e n c e of the interleukin-2 receptor [27]. The functional properties o f the T cell subpopulations stained by these m A b s h a v e b e e n described in a limited n u m b e r o f studies [1,4,16,22,23,28].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation